First Insights Into the Fine-Scale Movements of the Sandbar Shark, Carcharhinus plumbeus - Andrzejaczek, Samantha; Gleiss, Adrian C.; Pattiaratchi, Charitha B.; Meekan, Mark G. (Frontiers in Marine Science, 2018)
The expanding use of biologging tags in studies of shark movement provides an opportunity to elucidate the context and drivers of fine-scale movement patterns of these predators. In May 2017, we deployed high-resolution biologging tags on four mature female sandbar sharks Carcharhinus plumbeus at Ningaloo Reef for durations ranging between 13 and 25.5 h. Pressure and tri-axial motion sensors within these tags enabled the calculation of dive geometry, swimming kinematics and path tortuosity at fine spatial scales (m-km) and concurrent validation of these behaviors from video recordings. Sandbar sharks oscillated through the water column at shallow dive angles, with gliding behavior observed in the descent phase for all sharks. Continual V-shaped oscillatory movements were occasionally interspersed by U-shaped dives that predominately occurred around dusk. The bottom phase of these U-shaped dives likely occurred on the seabed, with dead-reckoning revealing a highly tortuous, circling track. By combining these fine-scale behavioral observations with existing ecological knowledge of sandbar habitat and diet, we argue that these U-shaped dives are likely to be a strategy for bentho-pelagic foraging. Comparing the diving geometry of sandbar sharks with those of other shark species reveals common patterns in oscillatory swimming. Collectively, the fine-scale movement patterns of sandbar sharks reported here are consistent with results of previous biologging studies that emphasize the role of cost-efficient foraging in sharks.